Research on Optimization Method of Non-Excavation Crossing Magnetic Target Parameters - HUANG Yang; CHE Yang; FENG Fuping; JIANG Chunlei; DU Weiqiang; ZHANG Zhengju (Cejing jishu)
In view of the problem that the magnetic induction intensity of the magnetic target cannot continue to increase like the theoretical value due to the existence of magnetic saturation, and the theoretical guidance range of the magnetic target is different from the actual value, this study proposes a magnetic target parameter optimization method considering the magnetic saturation phenomenon. Firstly, the main factors affecting the guiding range of magnetic targets during non-excavation engineering are analyzed by combining theoretical analysis, numerical simulation and indoor experiment. Then, on this basis, set the restrictions of other parameters, and perform simulation calculations by modifying the values of the main factors. Finally, the power of each scheme is compared, and the scheme with the least power is selected as the final optimization scheme. The simulation results show that compared with the theoretical analysis, the numerical simulation can better consider the magnetic saturation phenomenon. The main factor affecting the guiding range of the magnetic target is the length of the core, and when the core volume is the same, the greater the diameter ratio of the core length, the greater the magnetic field strengthening coefficient. The results show that numerical simulation methods are more suitable for the analysis of magnetic targets when magnetic saturation occurs.